Earthquake Damage Reduction in Timber Frame Houses Using Small-Size Fluid Damper - Nakamura, Yutaka; Fujii, Hinako (Frontiers in Built Environment, 2021)
Timber frame structures are common traditional methods of housing construction, which use squared-off timber beams, columns, and walls as lateral load-bearing members. The seismic performance of timber frame houses can be secured by the load-bearing capacity of erected braces and walls; however, past major earthquakes have caused severe damage to earthquake-resistant timber frame houses. This study investigates the effect of small-size fluid dampers on the earthquake damage reduction in a timber frame house through earthquake response analyses. A detailed analytical model was generated based on an actual two-story timber frame house, which was designed for the highest seismic grade using the latest Japanese standards. Time-history response analyses were carried out for the analytical model subjected to the 2016 Kumamoto earthquake with and without small-size fluid dampers. The small-size fluid damper is equipped with a relief mechanism for the damping force, and its damping property can be expressed using the Maxwell model. Four or seven fluid dampers were installed in the 1st story of the model to investigate their effect on the earthquake damage reduction. The results of the earthquake response analyses show that the four and seven fluid dampers can reduce the maximum 1st-story drift angle by approximately one-third and half, respectively. The dampers suppress the residual deformation, control the elongation of the fundamental period during the response, and restrain the amplitude growth. A small-size fluid damper has an equivalent quake resistance to a conventional structural wall with a wall ratio of 3 plus.